Governance, Politics and Antecedents of Gender Behavioural Flexibility in Africa - Fagbemi, Funmi Mowaiye - (NIU Journal of Humanities, 2018)
The coming of western and eastern cultures changed the â€œfaceâ€ of Africa and brought in a new dispensation which eroded what was in operation hitherto in Africa.  Women became relegated to the background in the scheme of influence.  The situation was worsened because written records were not available before the coming of foreign cultures. Necessary efforts for proper documentation by the new elites in Africa for hitherto â€˜erasedâ€™ history in Africa have also been poor.  This paper is intended as gap-filling in this regard.  It delves into â€˜gender blindnessâ€™ governance and politics before foreign infiltrations.